Would you mind? Evaluating User Acceptance and Usability of a Brain-Interface System in an Industrial Scenario - Coelho, Mateus Nazario; Jardim, João Victor; Silva, Mateus Coelho; Glass, Roberta; Silvas, Flávia; Delabrida, Saul (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Industry new ages demand its operator knowledge and mastery of interaction with emergent technologies. Virtual Reality (VR), Augmented Reality (AR), the Internet of Things (IoT), and Brain-Computer Interface (BCI) are some examples of technologies that are shaping how humans interact with industrial systems. VR technologies and BCI have become more prevalent due to price reduction and ergonomics. This work evaluates a VR scenario controlled by users using a brain-interface system. We explore a real-world mining industry case reproduced in an immersive environment. This study aims to evaluate users’ usability and acceptance of technology. Data from 26 participants were analyzed to investigate how prior VR experience influenced perceptions of usability (via SUS scores) and technology acceptance factors (via TAM questionnaire), including perceived ease of use (PEOU), perceived usefulness (PU), attitude toward use (ATU) and behavioral intention to use (BIU). The SUS average results (77.04 ± 14.79) and the ATU and BIU averages (4.52 and 4.60) indicate that the technology had an above-average global acceptance when compared with the literature, including an attitude and will to use the technology in the future. Statistical analyses include ANOVA and post-hoc tests to compare groups stratified by VR experience (novices to frequent users). ANOVA results demonstrated significant differences across VR experience groups: frequent users (>3 VR sessions) reported higher SUS scores (M = 90) and TAM ratings (e.g., BIU: M = 4.75) compared to novices (SUS: M = 65; BIU: M = 3.5). Qualitative feedback collected after the experiments highlighted usability barriers for novices, such as calibration delays and discomfort, while frequent users emphasized the system’s innovation.